A Critical Realist Exploration of Intergenerational Relations to Land in Small Scale Commercial Farming Families, Mushawasha Masvingo, Zimbabwe, 1953-2014 - Du Plessis, Irma (University of Pretoria, 2015)
Dissertation (MSocSci)--University of Pretoria, 2014.